Seabird ticks (Ixodes uriae) distribution along the Antarctic Peninsula - Barbosa, Andrés (2011)
The distribution of the tick Ixodes uriae is studied in the South Shetlands and different locations along the Antarctic Peninsula. Ticks were found beneath stones close to penguin rookeries of chinstrap, gentoo and adelie penguin, although no individuals were found parasitized. Our results showed that ticks are not distributed evenly along the Antarctic Peninsula being more common and abundant in the northern part with relative abundances of ticks ranging from 1 to 57 individuals per stone and from 2 to 26% of the stone inspected. Ticks are probably absent in the south.